Clinical and biochemical characteristics of newly diagnosed diabetics in South-South Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Diabetes mellitus (DM) patients are often referred to tertiary care centre after prior management in a primary or secondary health centre. Data on newly diagnosed DM are few in our locality.Objective:To determine the clinical and biochemical characteristics of newly diagnosed DM.Subjects and Methods:The present study was a retrospective study of newly diagnosed DM patients seen at a tertiary hospital in Nigeria. Data on patient's age, sex, body mass index (BMI), waist circumference, blood pressure, fasting plasma glucose and fasting lipid profile were retrieved and extracted from their medical records.Results:One hundred and thirty patients with DM were recruited in the study. Seventy-nine (60.8%) diabetic subjects were females. The mean ± standard deviation age of all the diabetic subjects was 55.09 ± 12.56 years. Obesity and hypertension were found in 34 (26.2%) and 50 (38.5%) of the diabetics, respectively. Female diabetic patients had significantly larger mean BMI than that of the male diabetics. High-density lipoprotein cholesterol dyslipidaemia, low-density lipoprotein-cholesterol dyslipidaemia, serum total cholesterol dyslipidaemia and triglyceride dyslipidaemia were found in 38 (29.2%), 35 (26.9%), 17 (13.1%) and 12 (9.2%) of diabetics, respectively.Conclusion:Hypertension, obesity and dyslipidaemia are common features in persons with newly diagnosed DM.